Implementation of android-based online presence to improve teacher work discipline - Khanifah, Sri; Hidayati, Dian (Edukasi, 2023)
This research is research on the use of Android-based online presence for teachers at SD Muhammadiyah Sukorejo, Sukorejo District, Kendal Regency to improve work discipline. The aim of this research is to explain how to implement Android-based online attendance and describe teacher discipline and performance. The theoretical study used in this research is the theory of work discipline put forward by Gorga that discipline is the attitude or behavior of an employee which is manifested in the form of a willingness with full awareness and sincerity to comply with and carry out duties and responsibilities in an effort to contribute as much as possible. . to achieve institutional goals. This research uses a qualitative approach using a phenomenological case study research model. The results of this research explain the use of Android-based online presence . Every working day, all teachers and employees at SD Muhammadiyah Sukorejo fill out the attendance list using the presence application installed on their cellphones . Through this application, attendance times and location coordinates where teachers and employees make attendance are recorded automatically and accurately. Through the use of online attendance, teacher discipline is better than before. In the last six months, data delays have decreased quite significantly from 22.2% to 6.6%. Online presence using an Android smartphone has a big impact on improving the discipline and performance of teachers and employees, although it still needs improvement.